Manajemen Kurikulum Merdeka Belajar dalam Penguatan Profil Pelajar Pancasila di MIN 1 Banyumas - Nafi'ah, Khoirotun (Jurnal Kependidikan, 2023)
The curriculum is present as a guide used by educators where the curriculum has undergone various changes as a form of adaptation to a dynamic era. One of them is by implementing an independent learning curriculum where this curriculum tends to be considered new and is still in the process of being implemented in stages. Nevertheless, not a few schools have implemented an independent learning curriculum that emphasizes independent learning according to the needs and characteristics of students. Therefore, researchers want to know about the implementation of the independent learning curriculum in increasing student understanding, where this research was conducted at MI N 1 Banyumas. The purpose of this research is to find out the impact of implementing the independent learning curriculum. On the other hand, the head of the madrasa also plays an important role in the running of the independent curriculum for the development of P5 at MI N 1 Banyumas. Keywords: Madrasah Principal Management, Independent Curriculum, P5